From Speaking Skills to Virtual Mobilities: Challenges of VR Technologies in Communication from the European University of Technology - Ciupe, Aurelia; Munteanu, Sonia; Parmaxi, Antigoni; Nicolaou, Anna; Gabaudan, Odette; Nocchi, Susanna; Schalk, Ana; Orza, Bogdan; Campian, Cristina; Maraciuc, Claudia (My University, 2023)
Within the vision of the European University of Technology (EUt+), a University Alliance of 8 European partners, augmenting a Mobility Friendly Plan through a virtual worlds approach, helps prepare students to overcome communication, language and cultural barriers. Such virtual environments can allow students to be immersed in the academic environments of the destination location, creating spaces for team building, collaboration, and creative activities. In the context of effective social interaction, communication and language learning become key pillars. Technological means that develop key competencies and abilities in such immersive environments, should be tackled. The current paper describes three uses cases of VR environments from the European University of Technology Alliance, implemented with the purpose of facilitating communication skills to overcome language and cultural barriers. The application of various technology levels, from prototype-based to customization of existing platforms is analyzed, under a TAM adoption assessment, to identify common challenges that may accompany the development of a shared VR campus, intended for effective communication, while providing the students a feeling of comfort, safety and confidence.
Keywords: communication skills; immersive experiences; language confidence; language learning; public speaking; student mobilities; Virtual Reality